Mechanical properties and stress-strain relationship of early strength polymer-modified concrete at different ages - Gu, Jiawei; Jia, Xing; Che, Jialing; Chin, Siew Choo (Elsevier Ltd., 2025)
Early-strength polymer-modified concrete (ES-PMC) has demonstrated considerable promise for rapid repair applications, where its performance is critical to ensuring the safety and quality of concrete structure construction. This study examines the mechanical properties and stress-strain behavior of ES-PMC at various curing ages (1.5 h, 2 h, 3 h, 1 day, 3 days, 7 days, and 28 days), with early-strength concrete (ESC) serving as the control group. The results indicate that ES-PMC generally surpasses ESC in terms of cube compressive strength, uniaxial compressive strength, and flexural strength, achieving values of 35.8 MPa, 25.4 MPa, and 4.4 MPa, respectively, at 2 h. Furthermore, a strong linear correlation is observed between the cube compressive and uniaxial compressive strengths of both ESC and ES-PMC. Under uniaxial loading, as the curing age increases, both materials undergo greater damage, with peak stress, elastic modulus, and toughness increasing over time, while peak strain, ultimate strain, and relative energy absorption capacity decrease. Additionally, a modified stress-strain model for ES-PMC was developed, incorporating age-related factors to accurately depict its stress-strain behavior across different ages. This model provides a theoretical basis for promoting its application in practical engineering and predicting its performance at various stages.